(untitled) (Revista Contexto & Educação, 2024)
This article aims to analyze the perceptions of science of a group of teachers of Basic, Technical and Technological Education who are divided regarding the conceptions and practices about experimentation in teaching. The research has a qualitative approach and is descriptive. The participants were14 professors linked to the Federal Institutes of the State of Goiás, and the data were collected through a semi-structured interview. For data analysis, the interviews were transcribed, submitted to the IRAMUTEQ software and analytical interpretation. Our results explore the similarities and distances between four groups that present different stylistic principles about experimentation in teaching. Among the groups that approach simplistic stylistic principles of experimentation, there is a defense for the neutrality of science, considering the subjective aspects that involves doing science as a negative characteristic. In counterpoint, the group that approaches contemporary stylistic principles of experimentation perceives subjective aspects as inherent to science. From the data presented, we can say that the perception of science is a strong conditioning factor to the perpetuation of simplistic conceptions and teaching practices when it comes to experimentation in teaching.